(6x+8)+(-7x-11)=

Simple and best practice solution for (6x+8)+(-7x-11)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+8)+(-7x-11)= equation:


Simplifying
(6x + 8) + (-7x + -11) = 0

Reorder the terms:
(8 + 6x) + (-7x + -11) = 0

Remove parenthesis around (8 + 6x)
8 + 6x + (-7x + -11) = 0

Reorder the terms:
8 + 6x + (-11 + -7x) = 0

Remove parenthesis around (-11 + -7x)
8 + 6x + -11 + -7x = 0

Reorder the terms:
8 + -11 + 6x + -7x = 0

Combine like terms: 8 + -11 = -3
-3 + 6x + -7x = 0

Combine like terms: 6x + -7x = -1x
-3 + -1x = 0

Solving
-3 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -1x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 0 + 3
-1x = 0 + 3

Combine like terms: 0 + 3 = 3
-1x = 3

Divide each side by '-1'.
x = -3

Simplifying
x = -3

See similar equations:

| 4p+3=.8 | | 4(4/5)+4(-9/5)=-4 | | (x+4)/(4)=(x)/(x-2) | | 9-12+5= | | cx-y=2 | | (x-3)-9=0 | | 9p+5.8= | | 4(4/5)-(-9/5)=5 | | 7x+9y-6x-11y= | | 60x-60x^3=0 | | 9p+4=5.8 | | 9--12+5= | | 2x-((3x^2)/36) | | 9/4y=2/3y | | 5y+2=4.5 | | -7+2x-5x=-7 | | y=4(4/5)-5 | | 6-3(x+2)=12 | | -6a-a= | | 2k+3=5.4 | | 36t^2/3+36t^1/3+9=0 | | -1/5(n+2)=10 | | 2k+5.4=3 | | 114/14 | | -1.5(n+2)=10 | | 2x^2+4=4x^2-8x+4 | | 49/98=8/12 | | 3k+2=5.4 | | (2+-6)=-24 | | 2x-y+9=0 | | 5/4x+1/8x+5/8+x | | 3/2x+1/3x=1/3 |

Equations solver categories